A fundamental paradigm for coral reef carbonate sediment dissolution - Andersson, Andreas J. (Frontiers in Marine Science, 2015)
The long-term success of coral reefs depends on a positive balance of calcium carbonate production exceeding dissolution, erosion, and material export. As a result of ocean acidification, coral reefs could transition from net accretion to net erosion owing to decreasing rates of calcification and increasing rates of chemical dissolution and bioerosion. Here, I present a fundamental paradigm that aims to explain the main driver of carbonate sediment dissolution on coral reefs based on theory and a new empirical dataset of pore water carbonate chemistry from the Bermuda coral reef platform. The paradigm shows that carbonate sediment dissolution is most strongly controlled by the extent of organic matter decomposition in the sediments, but that the magnitude of dissolution is influenced by how much decomposition is required to reach pore water undersaturation with respect to the most soluble bulk carbonate mineral phase present in the sediments, a condition defined as the Carbonate Critical Threshold (CCT). Decomposition of organic matter beyond the CCT under aerobic conditions results in stoichiometric proportional dissolution of carbonate sediments. As ocean acidification proceeds over the next several decades, the extent of organic matter decomposition required to reach the CCT will decrease, carbonate dissolution will increase, and subsequently the accumulation of carbonate sediments will decrease. Since drastic reductions in anthropogenic CO2 emission are unlikely in the foreseeable future, the paradigm shows that active controls and reduction of organic matter input to coral reefs at the local scale might be an effective mitigation strategy to prevent or delay coral reefs transitioning to a state of net dissolution.